Sustainable Prosperity in the New Economy? Business Organization and High-Tech Employment in the United States - Lazonick, William (W.E. Upjohn Institute, 2009)
Lazonick explores the origins of the new era of employment insecurity and income inequality, and considers what governments, businesses, and individuals can do about it. He also asks whether the United States can refashion its high-tech business model to generate stable and equitable economic growth.